Organic paddy farming practice to learning application - Othman, Zakirah; Muhammad, Amran (2012)
Knowledge sharing and transfer through information and communication technology applications is alternative and popular medium in this era.This paper aim to describe how the knowledge about organic paddy practices are used in learning prototype, call as Si Padi.The objective of learning prototype is to increase awareness and to promote sustainable practices in organic paddy farming. The real-life practices of sustainable paddy farming have been adapted in the design of the prototype.The findings of this study indicate that the prototype is beneficial in creating sustainability awareness among the students. For future applications, the learning prototype for the sustainability awareness program can be extended to other sustainability related issues.